1994
DOI: 10.1161/01.str.25.6.1165
|View full text |Cite
|
Sign up to set email alerts
|

Stroke incidence and mortality in rural and urban Shanghai from 1984 through 1991. Findings from a community-based registry.

Abstract: Mortality from stroke has declined in many countries. This decline may result from a fall in incidence of stroke or a decrease in case fatality from stroke. The present study was conducted to investigate the temporal trends of incidence rate, mortality rate, and case fatality of stroke in an urban and rural Chinese population. A community-based registry study was established in 1983 in defined rural and urban areas of Shanghai with a population aged 35 to 74 years of approximately 86,000 subjects, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Death rates in our trial were low when compared with casefatality rates reported in epidemiological studies. 1 However, our results are consistent with recent data from the nationwide China National Stroke Registry, whereby 22.5% of patients with ICH died at 6 months. 28 Our low death numbers may have been because of selection bias based on (1) our exclusion criteria such that severe cases were excluded; (2) differences in socioeconomic status (participants had above average earnings and socioeconomic status); and (3) the characteristics of the hospitals involved in our trial.…”
Section: Limitationssupporting
confidence: 92%
See 1 more Smart Citation
“…Death rates in our trial were low when compared with casefatality rates reported in epidemiological studies. 1 However, our results are consistent with recent data from the nationwide China National Stroke Registry, whereby 22.5% of patients with ICH died at 6 months. 28 Our low death numbers may have been because of selection bias based on (1) our exclusion criteria such that severe cases were excluded; (2) differences in socioeconomic status (participants had above average earnings and socioeconomic status); and (3) the characteristics of the hospitals involved in our trial.…”
Section: Limitationssupporting
confidence: 92%
“…[1][2][3][4] In absolute terms, this equates to large numbers of cases in China, and interventions to reduce the effects of ICH are important to determine. This is because ICH is generally more severe than ischemic stroke 5 and is associated with poorer functional outcome and higher case-fatality.…”
mentioning
confidence: 99%
“…1,2 The risk factor profiles and prevention strategies are different for ischemic and hemorrhagic stroke, 3 so it is important to clarify the proportion of stroke subtypes. Most previous studies suggested that at least 30% of strokes in China were hemorrhagic strokes 4,5 ; some studies even reported that Ͼ50% of strokes were hemorrhagic, 6 which was significantly different from the findings in whites. [7][8][9][10][11][12][13][14][15][16] However, most of these previous studies either limited the study population to a confined area or based the diagnosis criteria mainly on clinical presentations.…”
mentioning
confidence: 87%
“…[7][8][9][10][11][12][13][14][15][16] Previous studies in China, Hong Kong, Taiwan, and Japan generally found that 23% to 52.2% of strokes were hemorrhagic, [3][4][5][6][21][22][23][24][25] in contrast to only 9% to 18% in whites. [7][8][9][10][11][12][13][14][15][16] In the present study, 29.6% of stroke cases overall in 2000 were hemorrhagic in Chinese populations, which supported the above idea that an ethnic difference existed between Eastern and Western populations.…”
Section: Stroke Subtypes In Chinese Populations Compared With Westernmentioning
confidence: 99%
“…The previous studies suggested that at least 30% of strokes in China were HS (Hong et al. 1994). The risk factor profiles and prevention strategies are different for ischemic and hemorrhagic stroke (Leppala et al.…”
Section: Introductionmentioning
confidence: 99%